STRATEGI PEMASARAN BERBASIS SYARIAH UNTUK PRODUK UMKM UNTUK MENGUATKAN EKOSISTEM EKONOMI LOKAL - Yunas, Muhammad Faisal (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to examine how marketing strategies for MSME products based on sharia principles can strengthen the local economic system. The study uses quantitative methods and purposive sampling techniques. This study also seeks to determine how the application of sharia principles in marketing can increase the competitiveness of MSMEs and encourage sustainable local economic growth. Data was obtained from a survey conducted on 78 respondents who are MSME actors in Bojong Kulur, Bogor, West Java, Indonesia. The data was analysed using multiple linear regression to determine the relationship between the variables of sharia marketing strategy, local ecosystem support, and economic outcomes. The results show that sharia-based marketing strategies do not contribute significantly to strengthening the local economic system. This study also provides practical suggestions for SME actors and policymakers to integrate sharia principles into their business strategies.